2014
DOI: 10.1098/rsfs.2013.0060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of filopodium-like protrusion and endothelial cellular motility on one-dimensional extracellular matrix fibrils

Abstract: Endothelial filopodia play key roles in guiding the tubular sprouting during angiogenesis. However, their dynamic morphological characteristics, with the associated implications in cell motility, have been subjected to limited investigations. In this work, the interaction between endothelial cells and extracellular matrix fibrils was recapitulated in vitro, where a specific focus was paid to derive the key morphological parameters to define the dynamics of filopodium-like protrusion during cell motility. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Similar actin-based waves have been observed during neuron extension and axonogenesis in vivo ( Edmondson and Hatten, 1987 ; Flynn et al, 2009 ; Govek et al, 2011 ). By observing these fin-like protrusions at a high spatio-temporal resolution, we were able to determine that these fins guide cell migration along fibers but also analyze their dynamics, a finding that has not been reported in previous studies ( Lee et al, 2013 ; Sharma et al, 2013 ; Xue et al, 2014 ; Higgins et al, 2015 ). Importantly, our study demonstrated that these waves of fin-like protrusions are exhibited and used by a variety of cell types, including endothelial, glioma, and fibroblast cell lines (Table S1), suggesting that is a widely used mechanism for fibrillar migration.…”
Section: Discussionmentioning
confidence: 88%
“…Similar actin-based waves have been observed during neuron extension and axonogenesis in vivo ( Edmondson and Hatten, 1987 ; Flynn et al, 2009 ; Govek et al, 2011 ). By observing these fin-like protrusions at a high spatio-temporal resolution, we were able to determine that these fins guide cell migration along fibers but also analyze their dynamics, a finding that has not been reported in previous studies ( Lee et al, 2013 ; Sharma et al, 2013 ; Xue et al, 2014 ; Higgins et al, 2015 ). Importantly, our study demonstrated that these waves of fin-like protrusions are exhibited and used by a variety of cell types, including endothelial, glioma, and fibroblast cell lines (Table S1), suggesting that is a widely used mechanism for fibrillar migration.…”
Section: Discussionmentioning
confidence: 88%
“…Endothelial filopodia serve as antennae, detecting chemical and mechanical cues in the environment. Motility is directed by anchoring filopodial protrusions and subsequent retraction of the cell body, moving the cell forward . Further studies will need to explore whether the effect we observed in the VCAM depleted cells is secondary to decreases in soluble VCAM expression, or if cell surface VCAM has a previously unrecognized function in mediating appropriate sensing and anchoring of filopodia.…”
Section: Discussionmentioning
confidence: 89%
“…The available surface is then too small to allow cells' lamellipodium to develop sufficient adhesions, leading to the unstable protrusions/retraction cycles (49,50). As it becomes denser, the whole monolayer then undergoes strong morphogenetic movements that eventually lead to cyst formation at the cone tips.…”
Section: Discussionmentioning
confidence: 99%